ANALISIS KADAR HIDROKUINON PADA KRIM MALAM DI KLINIK KECANTIKAN KABUPATEN BREBESDENGAN SPEKRTOFOTOMETRI UV-VIS - Prihastini Setyo Wulandari; Aulia Rahman; Pudjono Pudjono (Jurnal Farmasi Universitas Peradaban, 2021)
Phenol derivatives that are often misused as active ingredients in making beauty creams that function to whiten facial skin areas, one of which is hydroquinone. This compound is often applied as an active ingredient in the manufacture of night creams. These effects can begin to appear after using A period of 6 months and possibly irreversible. Aims to determine the content, levels, and safety level of facial whitening nights provided by doctors in beauty clinics. Six samples of night cream given by doctors from several regions will go through color, pH, and TLC tests. After that, it will be analyzed quantitatively using the visible spectrophotometry method. The analysis showed that all the cream samples analyzed were proven to contain hydroquinone, with each sample content of less than 1%. All samples of these creams should not be used as cosmetics but must be converted into the category of therapeutic products (drugs) or in other ways remove Hydroquinone ingredients from the formula if they are still produced in the cosmetic category.